Diagnostic performance of transvaginal ultrasound and magnetic resonance imaging for preoperative evaluation of low‐grade endometrioid endometrial carcinoma: prospective comparative study. (1st September 2021) - Cubo‐Abert, M.; Díaz‐Feijoo, B.; Bradbury, M.; Rodríguez‐Mías, N.‐L.; Vera, M.; Pérez‐Hoyos, S.; Gómez‐Cabeza, J.‐J.; Gil‐Moreno, A.
ABSTRACT: Objective: To compare the diagnostic performance of transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) in the prediction of deep myometrial invasion (DMI) and cervical stromal invasion (CSI) in patients with low‐grade (Grade 1 or 2) endometrioid endometrial cancer (EEC). Methods: This was a prospective study including all patients with low‐grade EEC diagnosed between October 2013 and July 2018 at the Vall d'Hebron Hospital in Barcelona, Spain. Preoperative staging was performed using TVS and MRI, followed by surgical staging. Final histology was considered as the reference standard. Sensitivity, specificity, likelihood ratios and diagnostic accuracy were calculated for both imaging techniques in the prediction of DMI and CSI, and the agreement index was calculated for both techniques. The STARD 2015 guidelines were followed. Results: A total of 131 patients with low‐grade EEC were included consecutively. Sensitivity was higher for TVS than for MRI both for the prediction of DMI (69% (95% CI, 53–82%) vs 51% (95% CI, 36–66%), respectively) and CSI (43% (95% CI, 27–61%) vs 24% (95% CI, 12–41%), respectively). Specificity was similar for TVS and MRI in the prediction of DMI (87% (95% CI, 78–93%) vs 91% (95% CI, 82–96%)) and equal in the prediction of CSI (97% (95% CI, 91–99%) for both). The agreement index between TVS and MRI was 0.84 (95% CI, 0.76–0.90) for DMI and 0.92 (95% CI, 0.85–0.96) for CSI. Conclusions: The diagnostic performance of TVS is similar to that of MRI for the prediction of DMI and CSI in low‐grade EEC, and TVS can play a role as a first‐line imaging technique in the preoperative evaluation of low‐grade EEC. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.